2017
DOI: 10.1111/ger.12262
|View full text |Cite
|
Sign up to set email alerts
|

Sedation with orally administered midazolam in elderly dental patients with major neurocognitive disorder

Abstract: Sedation with orally administered midazolam seems to be effective and safe in dental treatment of uncooperative persons with major neurocognitive disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…The dose range in the current study (0.06 to 0.11 mg/kg) is wide and thus could be expected to have been a significant determinant of sedation depth. Interestingly, a similar disparity in the relationship between weight and response was found by Rignell et al who concluded that “poor and no acceptance were found among women with low weight and men with high weight 14 …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The dose range in the current study (0.06 to 0.11 mg/kg) is wide and thus could be expected to have been a significant determinant of sedation depth. Interestingly, a similar disparity in the relationship between weight and response was found by Rignell et al who concluded that “poor and no acceptance were found among women with low weight and men with high weight 14 …”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, a similar disparity in the relationship between weight and response was found by Rignell et al who concluded that “poor and no acceptance were found among women with low weight and men with high weight. 14 ” Lastly, the use of other sedative medication was included as a covariate in the regression model but was also not found to have a significant influence on sedation depth. Many patients in nursing homes use drugs that have interactions with benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But as it has a minimal effect on the cardiovascular system, it is a commonly used sedative in clinical practice [ 8 ], especially in young children. Research finds that Midazolam or a like drug alone is often ineffective [ 9 , 10 ], and therefore it is often used in combination with other drugs. Oral Midazolam in combination with intranasal DEX can largely increase the success rate of sedation and offers a good sedative outcome.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this phenomenon could be the greater likelihood of restlessness in younger patients. [ 15 ] Other explanations for the combined use of propofol and midazolam for sedation are related to factors such as oral health condition and dental treatments. The disease burden for patients with special needs was generally high.…”
Section: Discussionmentioning
confidence: 99%